Student’s Understanding of Islamic Religion Course Material With a Basic Semiotics Approach to Improve Reading Skills - Rosijanih Arbie; Ratna Puspitasari; Sadieli Telaumbanua; B.M.A.S. Anaconda Bangkara; Khasanah Khasanah (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This study aims to dig up information on how students understand Islamic religion courses by using a basic semiotic approach to improve security in reading skills in Islamic religious course content. We conducted a series of debriefings with students from Sam Ratulangi University in the city. We obtained the data and analyzed it under a phenomenological approach which involved, among other things, interpretation of data grouping data and concluding to gain an understanding of validly answering study questions. Based on the results of interviews and analysis as well as gold, we can conclude that the understanding of Islamic religious course texts among student participants in general Islamic religious courses is categorized as good where students use a basic symbiotic approach to understand Islamic religious texts even though they have little understanding of Islam—considering that the majority of students at Sam Ratulangi University are not many who adhere to Islam. These findings will provide a new understanding and support studying students' academic skills using a basic semiotic approach.